Yuni Purnama Sari DAMPAK LINGKUNGAN KERJA, LOCUS OF CONTROL DAN STRES KERJA TERHADAP KINERJA KEUANGAN KARYAWAN PT. CMS BENGKULU : Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *e-mail: yunipurnamasari677@gmail.com - Yuni Purnama Sari (Universitas Nahdlatul Ulama Sidoarjo, 2019)
The research conducted aims to analyze the influence of the work environment, locus of control and work stress on employee performance. The study was conducted on PT. CMS totaling 26 people. This type of research is a causal study with a quantitative approach with data collection instruments in the form of questionnaires. Data were analyzed using statistical regression tests with the help of SPSS software. The findings of the study, namely: (1) there is a positive influence of the work environment on employee’s financial performance with a significance of 0,000, (2) there is a positive effect of locus of control on employee’s financial performance with a significance of 0.003, (3) there is a negative influence of work stress on performance employees with a significance of 0,000.